Poly(ethylene glycol)‐containing hydrogels modulate α‐defensin release from polymorphonuclear leukocytes and monocyte recruitment. Issue 12 (26th June 2015) - Lieberthal, Tyler Jacob; Cohen, Hannah Caitlin; Kao, W. John
Abstract: Polymorphonuclear leukocytes (PMNs) release granule proteins as the first line of defense against bacteria and set up chemotactic gradients that result in monocyte infiltration to the site of injury. Although well established, the role of biomaterials in regulating adherent PMN degranulation and subsequent PMN‐monocyte paracrine interactions is less clear. The aim of this study was to determine how biomaterials affect the degranulation of selected biomarkers and downstream monocyte adhesion and transendothelial migration. Poly(ethylene glycol) (PEG)‐containing hydrogels (PEG and an interpenetrating network of PEG and gelatin) promote the release of the α‐defensins human neutrophil peptides 1–3, but not azurocidin or monocyte chemotactic protein‐1. Although human neutrophil peptides 1–3 are monocyte chemoattractants, no subsequent effects on monocyte transmigration are observed in static conditions. Under flow conditions, monocyte adhesion on human umbilical vein endothelial cells stimulated with tumor necrosis factor‐α is elevated in the presence of granule proteins from PMNs adherent on polydimethylsiloxane, but not from PMNs cultured on PEG hydrogels. These results suggest that PEG promotes PMN antimicrobial capacity without enhanced monocyte recruitment. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3772–3780, 2015.